Toothpaste
By combining hydrated silica and zeolite as toothpaste friction agent and controlling its particle size and hardness, the problem of insufficient cleaning effect of existing toothpaste or damage to teeth is solved. At the same time, the adsorption performance of zeolite is used to achieve effective hemostasis function and improve the overall performance of toothpaste.
Patent Information
- Application Number
- CN202510125178.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-18
AI Technical Summary
When cleaning teeth, existing toothpastes have insufficient friction or too strong friction, resulting in poor cleaning effect or damage to the teeth. The hemostatic function mainly depends on the ingredients of Western medicine and has limited effects.
Hydrated silica and zeolite compound are used as friction agents for toothpaste. By regulating the synergistic effect of particle size, Brinell hardness and content, an appropriate cleaning effect is achieved, and the adsorption and hemostasis properties of zeolite are used to assist hemostasis.
It achieves the ability to avoid tooth damage while ensuring cleaning effect, and has effective hemostasis function, improving the overall performance of toothpaste.
Smart Images

Figure BDA0005259930430000121 
Figure BDA0005259930430000141 
Figure BDA0005259930430000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oral care, in particular to toothpaste. Background Art
[0002] Toothpaste is an oral cleaning product that can clean the oral cavity, prevent tooth decay and keep breath fresh. Its main ingredients include abrasives, moisturizers and surfactants. Among them, abrasives, as an important component of toothpaste, are mainly used to remove dirt and plaque on the surface of teeth and have the effect of whitening teeth. However, if the friction of the abrasive is not good, the effect of whitening teeth is not obvious and the cleaning effect is not good. If the friction of the abrasive is too strong, it will damage the tooth surface and periodontal tissues and cause damage to the teeth. In addition, diseases such as gingivitis and periodontitis can cause gum inflammation, which is easy to bleed after being touched. At the same time, brushing too hard or using too hard toothbrush bristles may also damage the gums and cause bleeding. However, most of the current toothpastes use Western medicine ingredients to stop bleeding. Summary of the invention
[0003] Based on this, it is necessary to provide a toothpaste to address the above problems. By compounding hydrated silica and zeolite as abrasives, and regulating the particle size, Brinell hardness and content of the two for synergy, it can not only ensure the cleaning effect, but also will not damage the teeth due to excessive friction, and it also has a hemostatic function.
[0004] A toothpaste comprises, by mass fraction, at least 5% to 20% of hydrated silica and 5% to 15% of zeolite, wherein the average particle size of the hydrated silica is R1, the Brinell hardness of the hydrated silica is H1, the average particle size of the zeolite is R2, the Brinell hardness of the zeolite is H2, and 20μm≤R1≤40μm, 1μm≤R2≤10μm, 5≤R1 / R2≤20, 2.5HB≤H1≤3.5HB, 4.0HB≤H2≤6HB, and 1.3≤H2 / H1≤2.
[0005] In one embodiment, 4.0HB≤H2≤5.5HB.
[0006] In one embodiment, the mass fraction of hydrated silica in the toothpaste is less than or equal to the mass fraction of zeolite.
[0007] In one embodiment, the mass ratio of the hydrated silica to the zeolite is 1:1 to 1:3.
[0008] In one embodiment, the specific surface area of the zeolite is greater than or equal to 50 m 2 / g -1 ; and / or, the pore size of the zeolite is greater than or equal to 0.5 nm.
[0009] In one embodiment, the mass fraction of calcium ions in the zeolite is 0.5% to 3%.
[0010] In one embodiment, the zeolite is also loaded with strontium ions.
[0011] In one of the embodiments, 20 μm≤R1≤30 μm, 5 μm≤R2≤10 μm, and 1.5≤H2 / H1≤2.
[0012] In one embodiment, the mass fraction of strontium ions in the zeolite is 0.2% to 2.0%.
[0013] In one embodiment, the mass ratio of strontium ions to calcium ions in the zeolite is 1:1 to 4:1.
[0014] In the toothpaste of the present invention, hydrated silica and zeolite are compounded as abrasives. Firstly, the particle size of hydrated silica is controlled to be 20 μm to 40 μm, the Brinell hardness is 2.5 HB to 3.5 HB, and the mass fraction in the toothpaste is 5% to 20%. The particle size of zeolite is controlled to be 1 μm to 10 μm, the Brinell hardness is 4.0 HB to 6 HB, and the mass fraction in the toothpaste is 5% to 15%. Secondly, the particle size ratio of hydrated silica to zeolite is further controlled to be 5 to 20, and the Brinell hardness ratio of zeolite to hydrated silica is 1.3 to 2. Thus, when used, the hydrated silica drives the zeolite to perform rolling mechanical friction on the tooth surface, which is similar to the effect of a large gear driving a small gear to roll, rather than the effect of rolling friction alone. In this way, the cleaning effect can be guaranteed and damage to the teeth due to excessive friction can be avoided.
[0015] In addition, zeolite has excellent adsorption and hemostatic properties, and can assist hemostasis by adsorption, promoting wound healing, etc. When the toothpaste of the present invention uses zeolite as a friction agent, it can better assist hemostasis under the friction driven by hydrated silica. DETAILED DESCRIPTION
[0016] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0017] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0018] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0019] At present, the commonly used toothpaste abrasives are mainly hydrated silica (silicon dioxide), calcium carbonate, calcium hydrogen phosphate, calcium pyrophosphate or aluminum hydroxide, and each abrasive has different friction effects due to particle size and hardness. In order to ensure that the toothpaste does not damage teeth due to excessive friction while ensuring the cleaning effect, the toothpaste provided by the present invention includes at least hydrated silica and zeolite, and the hydrated silica and zeolite are compounded as abrasives, wherein the hardness of hydrated silica is generally lower than that of zeolite. Combining the characteristics of hydrated silica and zeolite, the toothpaste of the present invention meets the following conditions:
[0020] First, the mass fraction of hydrated silica in the toothpaste is controlled to be 5% to 20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., and the average particle size R1 of the hydrated silica is controlled to be in the range of 20 μm to 40 μm, for example, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm The Brinell hardness H1 of the hydrated silica is controlled within the range of 2.5HB to 3.5HB, for example, 2.5HB, 2.6HB, 2.7HB, 2.8HB, 2.9HB, 3.0HB, 3.1HB, 3.2HB, 3.3HB, 3.4HB, 3.5HB, etc.
[0021] Secondly, the mass fraction of zeolite in the toothpaste is controlled to be 5% to 15%, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., the average particle size R2 of the zeolite is controlled to be in the range of 1 μm to 10 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., and the Brinell hardness H2 of the zeolite is controlled Within the range of 4.0HB to 6.0HB, for example, 4.0HB, 4.1HB, 4.2HB, 4.3HB, 4.4HB, 4.5HB, 4.6HB, 4.7HB, 4.8HB, 4.9HB, 5.0HB, 5.1HB, 5.2HB, 5.3HB, 5.4HB, 5.5HB, 5.6HB, 5.7HB, 5.8HB, 5.9HB, 6.0HB, etc.
[0022] At the same time, the particle size ratio R1 / R2 of hydrated silica and zeolite is further controlled to be 5 to 20, for example, R1 / R2 is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc., and the Brinell hardness ratio H2 / H1 of zeolite and hydrated silica is 1.3 to 2, for example, H2 / H1 is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc.
[0023] Therefore, by compounding hydrated silica and zeolite as abrasives for toothpaste, and regulating the particle size, Brinell hardness and content of hydrated silica and zeolite for synergy, when used, the hydrated silica will drive the zeolite to roll mechanically on the surface of the teeth, which is similar to the effect of a large gear driving a small gear to roll, rather than the effect of friction alone. In this way, the cleaning effect can be guaranteed and damage to the teeth due to excessive friction can be avoided.
[0024] In addition, zeolite has excellent adsorption and hemostatic properties, and can assist hemostasis by adsorption, promoting wound healing, etc. When the toothpaste of the present invention uses zeolite as a friction agent, it can better assist hemostasis under the friction driven by hydrated silica.
[0025] Furthermore, when the Brinell hardness H2 of zeolite is controlled within the range of 4.0 HB to 5.5 HB, it is more effective to avoid damage to teeth due to excessive friction.
[0026] In the toothpaste of the present invention, the average particle size of hydrated silica is relatively large, and the average particle size of zeolite is relatively small. In view of the Brinell hardness characteristics of hydrated silica and zeolite, when the mass proportion of zeolite in the toothpaste is preferably greater than the mass proportion of hydrated silica in the toothpaste, the effect of mechanical friction of hydrated silica driving zeolite to roll on the tooth surface during use is better. Furthermore, the mass ratio of the hydrated silica to the zeolite is preferably 1:1 to 1:3, for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, etc.
[0027] Furthermore, it is preferred that the specific surface area of the zeolite is greater than or equal to 50 m 2 / g -1 ; and / or, the pore size of the zeolite is preferably greater than or equal to 0.5 nm, so that the zeolite can better adsorb dental plaque, pigments and odors on the tooth surface, help clean the tooth surface, maintain oral hygiene, and better assist in hemostasis.
[0028] When zeolite assists in hemostasis, it is related to the concentration of released calcium ions. In the present invention, since zeolite will roll mechanically and rub under the drive of hydrated silica, based on this method, the mass fraction of calcium ions in the zeolite is preferably 0.5%-3%, for example 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, etc. The concentration of calcium ions in the oral environment is better, the hemostasis is fast, and the effect is excellent.
[0029] Dentin hypersensitivity refers to the pain caused by temperature, mechanical, chemical and other stimuli when the enamel (also called enamel) of the teeth is gradually worn away to expose the dentin. For example, it is a momentary pain when eating foods with high sugar content, sour fruits or drinking cold water. At present, strontium salts are generally used as desensitizing agents in toothpaste. However, when the content of desensitizing agents such as strontium salts in toothpaste is high, the taste of toothpaste is not good when used.
[0030] In the present invention, it is further preferred that the zeolite is also loaded with strontium ions, and because the toothpaste of the present invention will produce the effect of hydrated silica driving the zeolite to perform rolling mechanical friction on the tooth surface when used, the zeolite of the present invention can dynamically and continuously release strontium ions, ensuring that the concentration of strontium ions in the oral environment is in a relatively stable state, which can not only avoid the problem of poor taste due to excessive concentration and improve the taste, but also ensure that strontium ions can be continuously and stably adsorbed onto enamel and dentin, react with carbonate to form insoluble salt strontium carbonate (SrCO3), and react with hydroxyapatite of dentin to form hydroxystrontium apatite (Ca3(PO4)Sr(OH)2), which has the effect of sealing dental tubules and mineralizing dentin, thereby slowing down the conduction of stimulation and improving the anti-allergic ability of teeth. It should be noted that this is a continuous and stable process, so the anti-allergic effect it brings is better.
[0031] In order to improve the rapid rolling of zeolite on the tooth surface driven by hydrated silica during brushing, effectively frictionally cleaning and dynamically and continuously releasing strontium ions, and ensure that strontium ions in the oral environment are adsorbed by dentin and seal the dental tubules in a short period of time during brushing, the average particle size R1 of the hydrated silica is further preferably 20μm to 30μm, the average particle size R2 of the zeolite is further preferably 5μm to 10μm, and the Brinell hardness ratio H2 / H1 of zeolite and hydrated silica is further preferably 1.5 to 2.
[0032] Furthermore, the mass fraction of strontium ions in the zeolite is preferably 0.2%-2.0%, for example 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc., which can better control the concentration of strontium ions in the oral environment.
[0033] It is understood that the strontium ions in the zeolite can be obtained by impregnating the zeolite in a strontium salt such as strontium chloride or strontium nitrate, and the concentration of the strontium salt and the number of impregnations can be adjusted to adjust the concentration of the strontium ions in the zeolite. Similarly, although the zeolite itself contains calcium ions, the calcium ion content in the zeolite can also be adjusted by impregnating the zeolite in a calcium salt such as calcium chloride.
[0034] Furthermore, it is preferred that the mass ratio of strontium ions to calcium ions in the zeolite is 1:1-4:1, so that the anti-allergic effect and hemostatic effect of the toothpaste can reach a better state.
[0035] It is understandable that, in addition to abrasives, toothpaste also includes moisturizers, thickeners, surfactants, and flavors, such as xanthan gum, glycerin, sorbitol, sodium lauryl sulfate, etc., which will not be described in detail in the present invention.
[0036] Hereinafter, the toothpaste will be further described through the following specific examples.
[0037] Example 1
[0038] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0039] Example 2
[0040] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 20 μm, Brinell hardness H1 is 2.5 HB), 7.05% zeolite (particle size R2 is 4 μm, Brinell hardness H2 is 4 HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0041] Example 3
[0042] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 40 μm, Brinell hardness H1 is 3.5 HB), 7.05% zeolite (particle size R2 is 2 μm, Brinell hardness H2 is 6 HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0043] Example 4
[0044] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 35 μm, Brinell hardness H1 is 2.8 HB), 7.05% zeolite (particle size R2 is 3 μm, Brinell hardness H2 is 5 HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0045] Example 5
[0046] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 40 μm, Brinell hardness H1 is 3.2 HB), 7.05% zeolite (particle size R2 is 8 μm, Brinell hardness H2 is 4.16 HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0047] Example 6
[0048] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 25 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 2 μm, Brinell hardness H2 is 4.5HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0049] Comparative Example 1
[0050] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 18.33% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), and 0.07% titanium dioxide (CI77891).
[0051] Comparative Example 2
[0052] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 18.33% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0053] Comparative Example 3
[0054] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 14.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 4.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0055] Comparative Example 4
[0056] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 4.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 14.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0057] Comparative Example 5
[0058] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 10 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0059] Comparative Example 6
[0060] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 1 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0061] Comparative Example 7
[0062] In terms of mass fraction, the toothpaste in this comparative example mainly consists of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 20 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0063] Comparative Example 8
[0064] In terms of mass fraction, the toothpaste in this comparative example mainly consists of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 2.5 HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4 HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0065] Comparative Example 9
[0066] In terms of mass fraction, the toothpaste in this comparative example mainly consists of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0067] The toothpastes of Examples 1 to 6 and Comparative Examples 1 to 7 were compared in terms of performance, wherein the cleaning (whitening) effect was compared using the Lobene stain area index after 8 weeks of use by patients with exogenously stained teeth, the hard particles were detected with reference to the 5.7 method of GB / T 8372-2017 standard to reflect the damage of the toothpaste to the teeth, and the in vitro coagulation time was used to detect the hemostatic effect. The results are shown in Table 1.
[0068] Table 1
[0069]
[0070] As can be seen from Table 1, by compounding hydrated silica and zeolite as abrasives for toothpaste and regulating the particle size, Brinell hardness and content of hydrated silica and zeolite for synergy, it is possible to ensure the cleaning effect and avoid damage to teeth due to excessive friction, while also having a hemostatic function.
[0071] Example 7
[0072] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 12.72% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 5.61% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0073] Example 8
[0074] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 9.41% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 8.92% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0075] Example 9
[0076] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 7.8% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 10.53% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0077] Example 10
[0078] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 6.92% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 11.41% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0079] Embodiment 11
[0080] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 5.15% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 13.18% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, and the mass fraction of calcium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0081] The toothpastes of Examples 7 to 11 were compared in performance using the same method as above. The results are shown in Table 2.
[0082] Table 2
[0083]
[0084] As can be seen from Table 2, when the mass proportion of zeolite in the toothpaste is greater than the mass proportion of hydrated silica in the toothpaste, the effect is better.
[0085] Example 12
[0086] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 0.5%, the mass fraction of strontium ions is 0.2%), and 0.07% titanium dioxide (CI77891).
[0087] Embodiment 13
[0088] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 1%, the mass fraction of strontium ions is 0.5%), and 0.07% titanium dioxide (CI77891).
[0089] Embodiment 14
[0090] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 1%, the mass fraction of strontium ions is 1.5%), and 0.07% titanium dioxide (CI77891).
[0091] Embodiment 15
[0092] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 0.5%, the mass fraction of strontium ions is 1.5%), and 0.07% titanium dioxide (CI77891).
[0093] Example 16
[0094] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 2%, the mass fraction of strontium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0095] Embodiment 17
[0096] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 35 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4HB, the mass fraction of calcium ions is 2%, the mass fraction of strontium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0097] Embodiment 18
[0098] In terms of mass fraction, the toothpaste in this embodiment is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 11.28% hydrated silica (particle size R1 is 30 μm, Brinell hardness H1 is 3HB), 7.05% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 4HB, the mass fraction of calcium ions is 2%, the mass fraction of strontium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0099] According to the method of YY / T 1829-2022, the toothpastes of Comparative Examples 1 to 2 and the toothpastes of Examples 12 to 18 were tested for the tubule sealing performance, and the hemostasis time was tested according to the above method. The results are shown in Table 3.
[0100] Table 3
[0101]
[0102] As can be seen from Table 3, after the addition of strontium ions in zeolite, the toothpaste has the effect of sealing the dental tubules and mineralizing the dentin, thereby improving the anti-allergic ability of the teeth. At the same time, by optimizing the concentration of strontium ions and calcium ions, as well as optimizing the particle size and Brinell hardness of hydrated silica and zeolite, the hemostatic effect and anti-allergic ability of the toothpaste can be further improved.
[0103] Comparative Example 10
[0104] In terms of mass fraction, the toothpaste in this comparative example is mainly composed of 0.28% xanthan gum, 15.52% water, 58.16% sorbitol, 3.52% polyethylene glycol-400, 0.70% glycerol, 0.42% cellulose gum, 0.35% sodium pyrophosphate, 0.10% trichlorogalactose, 0.08% sodium benzoate, 0.99% sodium lauryl sulfate, 0.78% flavor, 0.70% zinc citrate, 18.33% zeolite (particle size R2 is 5 μm, Brinell hardness H2 is 5.4 HB, the mass fraction of calcium ions is 2%, the mass fraction of strontium ions is 2%), and 0.07% titanium dioxide (CI77891).
[0105] The toothpastes of Example 16 and Comparative Example 10 were tested for taste. The test method was to select 50 volunteers and divide them into 2 groups, 25 people in each group, and use the toothpastes of Example 16 and Comparative Example 10 respectively to evaluate the taste. The results were as follows: the volunteers who used the toothpaste of Example 16 all said that the taste was good, while among the volunteers who used the toothpaste of Comparative Example 10, 8 people said that the taste was average, and 17 people said that the taste was not good. It can be seen that the abrasive combination of the present invention can make zeolite release strontium ions dynamically and continuously, ensure that the concentration of strontium ions in the oral environment is in a relatively stable state, avoid the problem of poor taste caused by excessive concentration, and improve the taste.
[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A toothpaste, characterized in that: In terms of mass fraction, it includes at least 5% to 20% of hydrated silica and 5% to 15% of zeolite, wherein the average particle size of the hydrated silica is R1, the Brinell hardness of the hydrated silica is H1, the average particle size of the zeolite is R2, the Brinell hardness of the zeolite is H2, and 20μm≤R1≤40μm, 1μm≤R2≤10μm, 5≤R1 / R2≤20, 2.5HB≤H1≤3.5HB, 4.0HB≤H2≤6HB, and 1.3≤H2 / H1≤2.
2. The toothpaste according to claim 1, characterized in that 4.0HB≤H2≤5.5HB.
3. The toothpaste according to claim 1, characterized in that The mass fraction of hydrated silica in the toothpaste is less than or equal to the mass fraction of zeolite.
4. The toothpaste according to claim 3, characterized in that The mass ratio of the hydrated silica to the zeolite is 1:1 to 1:
3.
5. The toothpaste according to claim 1, characterized in that The specific surface area of the zeolite is greater than or equal to 50 m 2 / g -1 ; and / or, the pore size of the zeolite is greater than or equal to 0.5 nm.
6. The toothpaste according to any one of claims 1 to 5, characterized in that: The mass fraction of calcium ions in the zeolite is 0.5% to 3%.
7. The toothpaste according to any one of claims 1 to 5, characterized in that: The zeolite is also loaded with strontium ions.
8. The toothpaste according to claim 7, characterized in that 20μm≤R1≤30μm, 5μm≤R2≤10μm, 1.5≤H2 / H1≤2.
9. The toothpaste according to claim 7, characterized in that The mass fraction of strontium ions in the zeolite is 0.2% to 2.0%.
10. The toothpaste according to claim 9, characterized in that The mass ratio of strontium ions to calcium ions in the zeolite is 1:1 to 4:1.
Citation Information
Cited By
toothpaste
EP4817591A1